The influence of creative task engagement on English L2 learners' negotiation of meaning in oral communication tasks. (February 2019) - Wang, Hung-chun
Abstract: This study investigates whether creative L2 tasks contribute to distinct interaction patterns among English L2 adult learners. With a focus on learners' negotiation of meaning, it probed learners' group interactions on two creative tasks and two controlled tasks. Each of these tasks included one decision-making task and one opinion-exchange task, resulting in four distinct task conditions. Thirty-six English majors solicited from two Taiwanese universities worked together in groups of four to complete all of the tasks. Results demonstrate that the creative tasks evoked significantly more instances of meaning negotiation than the controlled tasks. Moreover, the effect of creative tasks on the participants' use of distinct negotiation strategies varied by the types of tasks the participants undertook. Overall, by bridging theoretical work in creativity and L2 research, this study brings to light the influence of creative task engagement on adult learners' negotiation of meaning. Findings also suggest that teachers can provide creative tasks to stimulate learner interaction and encourage students to think creatively. The creative tasks developed in this study can also serve as a pedagogical model for teachers to design creative oral communication tasks based on their curricular objectives.